Moldova and the Transnistrian Conflict / Chapter 4 of Europeanization and Conflict Resolution: Case Studies from the European Periphery - Michael Emerson; Marius Vahl (Journal on Ethnopolitics and Minority Issues in Europe, 2004)
The Transnistrian conflict emerged with the dissolution of the Soviet Union in the late 1980s. The two sides have been unable to agree on any of the proposals tabled by the international mediators, Russia, Ukraine and the OSCE. The EU played a neglible role during the first decade of the Transnistrian conflict, but has recently become more engaged. This was preceded by a growing emphasis on the EU and Europeanization in Moldovan political discourse. Disillusionment with the negotiating format has grown in Moldova, increasing support for Europeanization of Moldova independently of the settlement of the conflict. The EU engagement has led to a growing resentment towards the EU in Transnistrian political discourse. Differences among the major external actors have become more pronounced, with Russia disapproving of the 'interference' of the West and the growing engagement of the EU.